Techno-Economic Analysis of Utilization of Tofu Production Liquid Waste into Liquid Organic Fertilizer Using Experimental Methods - Rini Gustiari (Journal of Economics Business Industry, 2023)
Tofu Industry is a company that produces liquid waste that has the potential to pollute the environment and is one of the industries that produces organic waste. The presence of organic elements in tofu liquid waste causes researchers to use tofu liquid waste into liquid organic fertilizer that has added value. This liquid organic fertilizer can be an alternative at a low price compared to other liquid organic fertilizers on the market. This liquid organic fertilizer is manufactured mainly from tofu liquid waste with coconut water, brown sugar solution, and EM4 solution. The method of making liquid organic fertilizer is a random design complete with three treatments. Each sample composition is 1 liter of liquid waste, 2 liters of liquid waste, and 3 liters of liquid waste. The laboratory test results show that in liquid organic fertilizer, N, P, and K show that treatment A has the best results with N values of 0.42%, P 0.13%, and K 0.29%. The results of the techno-economic analysis are that the cost of goods produced is obtained at Rp. 5,178.75 / liter, the break-even point of 95.58 liters, and it takes 42 days to break even. The payback period only takes 0.9 years. For further research, the process of making liquid organic fertilizer should produce samples on a large scale to minimize the calculation of techno-economic analysis in the direct labor wage section.